Manifestation of subacute cutaneous lupus erythematosus during treatment with anti-PD-1 antibody cemiplimab – a case report - Fietz, Simon; Fröhlich, Anne; Mauch, Cornelia; de Vos-Hillebrand, Luka; Fetter, Tanja; Landsberg, Jennifer; Hoffmann, Friederike; Sirokay, Judith (Frontiers in Immunology, 2023)
For the first time, we describe the arise and successful treatment of cutaneous lupus erythematosus in a patient treated with anti-programmed cell death 1 (PD-1) antibody cemiplimab.The anti-programmed cell death protein 1 (PD-1) antibody cemiplimab has shown promising results in the treatment of unresectable or metastatic squamous cell carcinoma, however, frequently leads to immune-related adverse events limiting therapy efficacy. Although cutaneous side effects are common, only very few cases of cutaneous lupus erythematosus have been reported under anti-PD-1 immunotherapy. So far, no case of cutaneous lupus has been described under treatment with cemiplimab.Case report: For the first time, Wwe report the case of a patient with advanced squamous cell carcinoma, who developed clinical and histological findings in sun-exposed skin that were consistent with anti-SS-A/Ro antibody-positive subacute cutaneous lupus erythematosus (SCLE) shortly under treatment with cemiplimab. Additionally, laboratory chemical analyses revealed a severe immune-related hepatitis without clinical symptoms.Both, the SCLE and the hepatitis, resolved after the administration of topical and systemic steroids and the discontinuation of anti-PD-1 therapy.Treatment with cemiplimab can be associated with the appearance of cutaneous lupus erythematosus in sun-exposed areas. Application of topical and systemic glucocorticoids can lead to a rapid resolution of the skin eruptions. Moreover, our case illustrates the possibility of simultaneously occurring severe immune-related adverse events.